Postrecession gentrification in New York city - Hackworth, Jason (2002)
Although multiple authors have identified changes to gentrification since the early 1990s recession, there is not yet a composite sketch of the process in its contemporary form. The author synthesizes the growing body of literature on postrecession gentrification and explores its manifestation in three New York City neighborhoods. The literature points to four fundamental changes in the way that gentrification works. First, corporate developers are now more common initial gentrifiers than before. Second, the state, at various levels, is fueling the process more directly than in the past. Third, anti-gentrification social movements have been marginalized within the urban political sphere. Finally, the landeconomics of inner-city investment have changed in ways that accelerate certain types of neighborhood change. - Reproduced.
Keywords: Urban renewal - United States; Urban renewal